KEJADIAN PENYAKIT COLIBACILLOSIS PADA UNGGAS DI PETERNAKAN JATMIKO PUTRA FARM BOKONG, MARGOMULYO, SEYEGAN, SLEMAN YOGYAKARTA - , SEPTIO WIRYAWAN; , drh. Bambang Sutrisno, M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Preparation of this thesis is taken from Job Training material on broiler farms (broiler) PT. Jatmiko Son Farm, Butt, Margomulyo, Seyegan, Sleman, Yogyakarta, 14 to 20 March 2011. The purpose of data collection is used to determine a disease caused by bacteria in poultry farms Colibacillosis Jatmiko Farm. Data taken through conservation practices and directly to the cage to see the state DOC, care, treatment and cure sick birds. Cases of the disease that often attacks the farm variety. The latest data on the disease affecting poultry breeding farm is Jatmiko Chronic Respiratory Disease (CRD), pullorum Disease, E. Coli, and Gumboro. Of the presentation shows that in the period of the last few years, the disease caused by E. Colibacilosis Coli most often attacked. The data were spread E. Coli serotypes Colibacillosis pathogen as the cause is dominant (51.5%), as well as other serotypes rest as much as 48.5%. The thing to do is maintain sanitation breeder cage as maintaining ventilation, cleanliness liter, regularly carry out disinfection of equipment and other facilities. It is no less important is to maintain the quality of feed and drinking water, as well as pay attention to the density of the cage.